Analyzing Product Defects in the Tempeh Production Process Using FTA and FMEA Methods in CV. Aderina - Adi Dharma*; Moch. Nuruddin (Universitas Syiah Kuala, 2023)
CV. Aderina is a Home Industry that produces tempeh and has a product quality problem that still causes defective products. The types of product defects that often occur are foreign object entry, blackish color, and maturity level. A very effective method to overcome these problems is the FTA (Fault Tree Analysis) and FMEA (Failure Mode and Effects Analysis) methods. The purpose of this research is to identify the types of defects and factors that cause the highest defects in tempeh products and provide recommendations for improvement to improve the quality of Tempe products. Foreign body entry is the highest type of tempeh product defect in October 2021 based on the Pareto diagram with the number of defective products, namely 356 pcs and a defect percentage of 47.72%. In the Fault Tree of Foreign Object Entry, the causes of defects that occur are caused by tools, human error, and the environment. Based on the FMEA method, the highest RPN value is obtained, namely the cause of defects in a less clean room with an RPN value of 189, and becomes a priority for improvement. By using the 5W + 1H approach, the proposed improvement that can be given is to carry out cleaning in all production rooms regularly by making a cleaning picket schedule.